2018
DOI: 10.12659/msm.908970
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor in Endodontic Treatment: Topographic Evaluation of Mandibular Posterior Teeth and Lingual Cortical Plate Using Cone Beam Computed Tomography (CT)

Abstract: BackgroundTopographic relationships of mandibular posterior teeth with mandibular cortical plate are extremely important both in terms of infection spread and endodontic and surgical procedures to be performed. The aim of this study was to determine the relationship between root apex of the mandibular posterior teeth and lingual plate of the mandible.Material/MethodsCBCT data of 138 patients were retrospectively analyzed. The topographic relationship between root apex and lingual plate was classified as non-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The use of cone beam computed tomography (CBCT) in implantology, oral surgery, periodontology, orthodontics, and endodontics has greatly improved treatment success 1–7 . CBCT is the scan of choice for implant treatment planning as it offers greater measurement accuracy at lower radiation dosage, reduced scan time, and reduced artifacts compared to 2D and conventional medical CT imaging 8–13 .…”
mentioning
confidence: 99%
“…The use of cone beam computed tomography (CBCT) in implantology, oral surgery, periodontology, orthodontics, and endodontics has greatly improved treatment success 1–7 . CBCT is the scan of choice for implant treatment planning as it offers greater measurement accuracy at lower radiation dosage, reduced scan time, and reduced artifacts compared to 2D and conventional medical CT imaging 8–13 .…”
mentioning
confidence: 99%
“…This information, depending on the extent of the root protrusion, could alter the treatment plan and prognosis of the tooth. In root apex fenestrations (Types I, IV and VI), the proximity of the apical region of the root to the cortical plates can facilitate the spread of an odontogenic infection and the involvement of adjacent facial spaces (9). According to the results, root apex fenestrations are particularly frequent in the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…Fenestrated roots are also at risk of irrigant extrusion into the soft tissues (7), displacement of intracanal medicaments and fractured root canal instruments, or subcutaneous emphysema, as the resistance beyond the apical foramen is reduced, and therefore, air can be easily forced into subcutaneous tissues (8,9). RF can also affect the outcome of conservative root canal treatment as well as all surgical procedures involving mucoperiosteal flaps, including surgical endodontic procedures, as they could lead to further resorption of a bone plate that already lacks support and nourishment from the bone marrow (10).…”
Section: Introductionmentioning
confidence: 99%
“…The mandible forms the lower portion of the jaw complex and supports mastication, speech and facial expressions. The alveolar processes of the mandible consist of buccal-lingual plates, inter-dental septa and inter-radic-ular septa (6). Several anatomical studies have shown major changes in the anatomy of the posterior mandible after tooth loss, with age and sex contributing little to these changes (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Nerve injury can lead to a partial or permanent paraesthesia, lingual plate perforation (LPP) and sublingual or submandibular hematomas, with excessive bleeding or infection (9)(10)(11). (Figure 1) These anatomical structures not only give rise to surgical complications during implant operations but also cause fracture of the lingual plate during extractions, thereby facilitating the dissemination of microorganisms and infection to other areas (6). Furthermore, in cases of fenestration in the lingual plate, displacement of endodontic materials and iatrogenic subcutaneous emphysema are possible complications (6).…”
Section: Introductionmentioning
confidence: 99%